IMPLEMENTASI KEPEMIMPINAN PENDIDIKAN DI SMP NEGERI 1 CANDIROTO KABUPATEN TEMANGGUNG - Aifa’iyah, Barorotul; Nina Oktarina; Fathur Rohman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This article describes a descriptive qualitative reseach on the leadership style of the principal of SMP Negeri 1 Candiroto Temanggung Regency in improving the quality of education. This reseach was conducted through observation, interview and literature study. The main problem faced is the implementation of practicing various leadership styles in institutions by adjusting the context of dynamic situation and conditions with the aim that education run effectively and efficiently. The purpose of this study is to understand how a leader leads an institution with a trait leadership approach with the implementation of democratic and transformational leadership styles to improve the quality of education. The trait leadership approach modified with democratic and transformational leadership styles can be applied by the principal with the aim of improving the quality of education and the performance of educators and education personnel. The main results show that the principal is able to apply the practice of various kinds of effective leadership styles by adjusting the situation and conditions according to the context of the problem, this is reflected in principal taking risks with confidence and authority and encouraging creativity, innovation and collaboration in learning so that there is an increase in the quality of learning in the learning environment of SMP Negeri 1 Candiroto. The conclusion of this study is that the trait approach with democratic and transformational leadership styles by the principal has a significant role in improving the quality of education at SMP Negeri 1 Candiroto and needs greater support from all school members and related parties to strengthen this practice.